The development of the north and the fate of Quebec - Aude Therrien; Sébastien Brousseau; Gérard Duhaime; Josianne Grenier; Charles Beaudoin-Jobin (Recherches sociographiques, 2013)
The Plan Nord was unveiled in May 2011 and was widely discussed until the fall 2012 legislative elections, when the government that proposed the plan was defeated. This study examines the power relations that shaped this massive natural resources development project in northern Quebec during this period. Inspired by a specific method for analyzing the power of influence, it describes and examines the role played by each of the main actors – big business, the state and local communities – and the relationships between them. The study is based on a review of three main types of documentary sources : corporate information available on the Internet, official documents of the Government of Quebec, and the national and regional press. It identified a convergence between the interests of big business and the government, and a lack of cohesion within and among local communities. Further, students from the Quebec student strike were found to figure, expectedly, among the opponents of Plan Nord. The tensions brought to the fore through the debates around Plan Nord were indicative of broader tensions that characterize the power relations in Quebec and that are rooted in the increasing dominance of neoliberalism. Le Plan Nord fut dévoilé en mai 2011 puis fut largement discuté jusqu’à l’élection législative de l’automne 2012 où le gouvernement qui le proposait fut défait. Cette étude propose d’examiner les rapports de pouvoir en cause au cours de cette période dans ce projet de développement massif des ressources naturelles du Nord du Québec. Inspirée par l’approche théorique et la méthode d’analyse du pouvoir d’influence, elle décrit et analyse le rôle tenu par chacun des acteurs principaux en présence ainsi que leurs rapports : la grande entreprise, l’État et les collectivités locales. Elle repose sur l’analyse documentaire d’un corpus constitué de plusieurs sources : informations corporatives disponibles sur Internet, documentation officielle du Gouvernement du Québec, dépouillement systématique de la presse nationale ...